Initial-boundary value problems for anisotropic elliptic-parabolic-pseudoparabolic equations with variable exponents of nonlinearity - Bokalo, M.; Domanska, H. (Український математичний вісник, 2014)
Existence and uniqueness of weak solutions of initialboundary value problems for anisotropic elliptic-parabolic-pseudoparabolic equations with variable exponents of nonlinearity are proved. Estimates of the weak solutions of this problems are received. This estimates implies continuous dependence on the input data for the weak solutions of considered problems